Investigation of a Crime of Rape Against Children in the Jurisdiction of The Balerang’s Corp (Case Study of The Rape Crimes on Behalf of Anngi Priya Utomo) - Rizko Syahputra (Advances in Police Science Research Journal, 2021)
Children are the successors of the nation's ideals in the future, but nowadays crimes against children are rampant, the rewards and punishments given must also provide strict sanctions and a deterrent effect on perpetrators of sexual intercourse with children. The trigger for sexual intercourse with children is masterminded by a number of factors and various reasons. There are also various motives for cases of sexual intercourse with children that have been found in the field, but in this thesis what will be discussed is how to analyze a case of sexual intercourse committed by a teacher against his students. The research was conducted in the jurisdiction of the Barelang Police. Theories used in this research are Legal Effectiveness Theory, Competency Theory, and Role Theory. The concept used is the concept of the victim, the concept of the crime of sexual intercourse, and the concept of the investigation. This research uses a qualitative approach with a case study method. In addition, it will also discuss the point of view of the PPA unit investigator who was unable to prove this crime of sexual intercourse to two other victims. The results of this study are a description of the crime of sexual intercourse against a child whose legal entanglement is not in accordance with what it should be and the investigation process that requires the ability of the investigator because the victim is a child, as well as factors that hinder the investigation, namely law enforcement factors and infrastructure factors. Therefore, the authors provide suggestions to improve the quality of law enforcement and improve infrastructure in accordance with applicable regulations.